2012
DOI: 10.1080/02607476.2012.733195
|View full text |Cite
|
Sign up to set email alerts
|

Criticality and the practice-based MA: an argument drawn from teaching on the Masters in Teaching and Learning (MTL)

Abstract: Article:Goddard, R. and Payne, M.I. orcid.org/0000-0002-1019-7375 (2013) Criticality and the practice-based MA: an argument drawn from teaching on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The university, through its academic practices, constructs desire through SCQF Level 11, as the operationalisation of masterliness in which the elusive concept of criticality is pervasive. An ambivalence emerges here in respect of the academy in which masterliness as critique is located in ‘a tradition of thought that does not subject itself to governmental imperatives’ (Goddard and Payne, , p. 126) yet in which it is also deeply implicated. This, of course, merits further inquiry in itself, but through it we see accomplishment and masterliness becoming articulated, by means of equivalence, within a discourse of career‐long learning as point‐de‐capiton .…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The university, through its academic practices, constructs desire through SCQF Level 11, as the operationalisation of masterliness in which the elusive concept of criticality is pervasive. An ambivalence emerges here in respect of the academy in which masterliness as critique is located in ‘a tradition of thought that does not subject itself to governmental imperatives’ (Goddard and Payne, , p. 126) yet in which it is also deeply implicated. This, of course, merits further inquiry in itself, but through it we see accomplishment and masterliness becoming articulated, by means of equivalence, within a discourse of career‐long learning as point‐de‐capiton .…”
Section: Concluding Discussionmentioning
confidence: 99%
“…‘Masterliness’, Goddard and Payne (, p. 126) argue, ‘cannot be sustained apart from a robust conception of criticality’. Masterliness requires: ‘a disposition to interrogate explicit claims to truth, to expose and examine the assumptions that underlie argument and, importantly a commitment to the notion that education is concerned with the fostering of liberty and civility’.…”
Section: Introductionmentioning
confidence: 99%
“…It seemed that higher education could be an embodiment of intellectual humility. However, the description of forces beyond the control of the lecturer and student (such as the marketisation of higher education) indicated that the embodiment of intellectual humility would require a largescale, cultural disinclination to the neoliberal 'marketisation' and self-censorship perceived to be permeating the experience of social science higher education (Goddard and Payne, 2013).…”
Section: Discussionmentioning
confidence: 99%